A comparative analysis of international frameworks for 21st century competences: Implications for national curriculum policies - Voogt, Joke; Roblin, Natalie Pareja (Journal of curriculum studies, 2012)
National curricula need to change drastically to comply with the competences needed for the 21st century. In this paper eight frameworks describing 21st century competences were analysed. A comprehensive search for information about 21st century competences was conducted across the official websites of the selected frameworks, resulting in 32 documents that were analysed in detail. Travers and Westbury's framework of curriculum representations was used to determine horizontal and vertical consistency between the frameworks. The frameworks were compared on their underlying rationales and goals, their definition of 21st century competences, and the recommended strategies for the implementation and assessment of these skills in educational practice. In addition three international studies were examined to analyse how various countries (EU member states, OECD countries) and schools (SITES studies) deal (or not) with 21st century competences. The findings indicate a large extent of alignment between the frameworks about what 21st century competences are and why they are important (horizontal consistency), but intentions and practice seemed still far apart, indicating lack of vertical consistency. The implications of the implementation of 21st century competences in national curriculum policies are discussed and recommendations are provided.